Correlation of levels of early second trimester beta-human chorionic gonadotropin levels with severity of preeclampsia - Kumari, Shilpa; Chaudhary, Gunjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hypertensive disorders in pregnancy remains a leading cause of maternal morbidity and mortality all over the world as per World Health Organization (WHO), affecting 5-10% of all pregnant women. Screening women at an early stage and preventing complications are corner stone in the management of pre-eclampsia. Several studies have proven the reliability of beta-human chorionic gonadotropin (β-hCG) as predictor of preeclampsia. In this study we aim to find the correlation of increasing levels of β-hCG with severity of preeclampsia. Methods: In this study serum β-hCG estimation was done in 200 pregnant women between 13 and 20 weeks of gestation, selected randomly over a period of 1 year attending antenatal clinic by quantitative determination of β-hCG by electro-chemiluminescence immunoassay. Multiple of median (MOM) is calculated from charts of norms available. They were followed till delivery for development of pre-eclampsia. The following patients were followed up till delivery. Blood parameters, blood pressure readings, were done at 34 weeks for every patient and maternal complications were noted and results were analysed statistically. Results: The incidence of preeclampsia in this study population was 8% (16 out of 200). This study found a significant correlation between increasing levels of MOM’s of β-hCG with the severity of preeclampsia. Conclusions: In this study, there was significant association between MOM values of β-hCG with the parameters defining severity of preeclampsia. The results of our study show β-hCG to be not only a reliable marker for prediction of preeclampsia, but also its severity.